Atomic force microscopic measurement of a used cylinder liner for prediction of boundary friction. (June 2019) - Bewsher, Stephen Richard; Leighton, M; Mohammadpour, Mahdi; Rahnejat, Homer; Offner, Guenter; Knaus, Oliver
Accurate simulation performs a crucial role in the design and development of new modern internal combustion engines. In the case of piston rings, simulations are used to effectively predict generated friction and power loss of proposed designs. These are consequences of viscous shear of a thin lubricant film, likewise boundary friction caused by direct interaction of piston rings with the cylinder liner/bore surface. The most commonly used model for determining boundary friction is that of Greenwood and Tripp. The model requires the pressure coefficient of boundary shear strength of asperities from the softer of the contacting surfaces as an input. This parameter needs to be measured. The paper describes the process of measurement using an Atomic Force Microscope (AFM), both for a dry surface and that wetted by the presence of a lubricant layer. For realistic results, the investigated specimen is a used, tested engine cylinder liner where boundary active lubricant additives are bonded to its surface as well as combustion products. This approach is as opposed to the previously reported works using new flat surfaces with base oil or partially formulated lubricants and has not been previously reported in the literature. The results show that for used cylinder liners, the measured boundary shear strength of asperities varies according to location along the stroke. Results are reported for the top dead centre, mid-stroke and bottom dead centre locations. The measurements are subsequently used with two-dimensional Reynolds solution for a top compression ring-liner contact, where it is found that accurate localised predictions of generated friction and power loss can be made instead of the usual average value approach reported in the literature.